Risk Factors for Measles Infection During Measles Outbreaks in Southeast Asia: Literature Review - Pebriyani Dwi Rakhmawati; Safira Balqis; Hana Amada Nafisyah; Fidyatus Sholihah; Afni Andini Rikawati; Rosita Dwi Jayanti; Dwi Sarwani Sri Rejeki (Epidemiology and Society Health Review (ESHR), 2026)
Background: Measles remains a major health problem in Southeast Asia due to high transmission rates. In 2025, Indonesia ranked seventh with 5,035 cases, while the 2020-2025 trend shows significant fluctuations in Indonesia, the Philippines, and Laos due to outbreaks during certain periods. This study aims to identify risk factors for measles infection during outbreaks in Southeast Asia through a literature review. Method: The literature review was conducted using databases of PubMed, ProQuest, ScienceDirect, and Google Scholar with measles related keywords. Full-text, open-access articles published within the last 10 years and originating from Southeast Asia were included. Of the 21,051 articles identified and seven articles met PRISMA criteria. Data were extracted, assessed using JBI checklist, and synthesized to identify measles risk factors. Results: The results showed that risk factors for measles during outbreaks included individual factors (young age, malnutrition, incomplete immunization, history of contact), health services (limited access, delayed treatment), environment (housing density), and socio-demographics (negative perceptions of immunization, indigenous peoples). Conclusion: Therefore, by identifying these risk factors, measles outbreak control in Southeast Asia can be focused on immunization, nutrition, health services, and community education.